Fabrication and biocompatibility of a 3D-printed porous Ti-25Ta alloy scaffold - Di Wu; Yada Li; Wangwei Zhu; Haolin Jiao; Bing Ge; Qinwen Xie; Jianfeng Xu; Weidan Wang; Fang Cao; Guangxiao Yin; Junlei Li; Dewei Zhao (Discover Applied Sciences)
Abstract In this study, a porous Ti-25Ta alloy scaffold was fabricated using additive manufacturing(AM) and compared with pure Ti to evaluate its biocompatibility and osteogenic potential. The scaffolds were fabricated using a Laser Beam Powder Bed Fusion process, followed by investigations of physical properties, in vitro cytocompatibility, osteogenesis, macrophage polarization, and in vivo bone reconstruction. Pure Ti exhibits the highest wettability, cell proliferation, osteogenic differentiation, mineralized nodule formation, anti-inflammatory capability, and bone reconstruction. The adoption of Ta in the Ti-25Ta alloy significantly increases its wettability, osteogenesis, and anti-inflammatory without a great increase in density. In summary, the Ti-25Ta alloy has a favorable balance of physical properties and biological performance, making it a promising candidate as a bone implant material.